Leveraging Systems Science to Promote the Implementation and Sustainability of Mental Health and Psychosocial Interventions in Low- and Middle-Income Countries. Issue 4 (July 2021) - Greene, M. Claire; Huang, Terry T. K.; Giusto, Ali; Lovero, Kathryn L.; Stockton, Melissa A.; Shelton, Rachel C.; dos Santos, Palmira; Saúte, Francisco; Wainberg, Milton L.
Abstract : Abstract: Advancements in global mental health implementation research have revealed promising strategies for improving access to evidence-based mental health care. These advancements have not translated, however, into a reduced prevalence of mental disorders. In this review we examine the relationships between determinants (i.e., barriers and facilitators) and outcomes of mental health services in low- and middle-income countries to identify opportunities for improving the population-level impact and sustainability of innovations in global mental health. We identified three key implementation and services outcomes that influenced the prevalence of mental disorders in the 56 included review articles: supply (access, implementation), demand (help seeking, utilization), and quality (effectiveness, quality of care) of mental health services. Determinants of these outcomes revealed seven themes: community stakeholder engagement; cultural relevance; stigma; human resource capacity; organization of services; governance, policy, and financing; and sociopolitical and community context. We developed a causal loop diagram to illustrate the relationships among these determinants and outcomes. The causal loop diagram revealed the central role of community stakeholder engagement in bridging implementation and patient outcomes, the importance of addressing stigma and social determinants of mental health, and the need to complement supply-side implementation strategies with approaches to equilibrate demand and improve the quality of services. Applying systems science methodologies to global mental health research presents an opportunity to examine the complex relationships among community and health system factors that influence implementation of evidence-based interventions in order to identify sustainable approaches to improve the population-level impact of mental health services in low- and middle-income countries. Abstract : Supplemental digital content is available in the text.